PERAN INDONESIA, MALAYSIA DAN SINGAPURA DALAM KESELAMATAN PELAYARAN DI SELAT MALAKA SEBAGAI SELAT INTERNASIONAL - Chylsia Felyaross Lasambouw; Evi Deliana; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The use of the sea in state life by countries around the world is regulatedby the United Nations Convention on the Law of the Sea 1982 (United NationsConvention on the Law of the Sea of 1982, abbreviated as UNCLOS 1982). One ofthe sea water areas that is the scope of the regulation by UNCLOS 1982 is thestrait used as an international shipping lane, the Strait of Malacca is one of them.As one of the busiest straits used as a shipping lane for international trade, theStrait of Malacca is seen as still having a lack of shipping security by shipownercountries that always sail through the Strait of Malacca, including Japan, and theUnited States. Based on geographical facts, the Strait of Malacca is part ofIndonesia, Malaysia and Singapura.This research is carried out based on the normative-juridical type ofresearch which means research conducted on legal principles that are dotted withthe provisions of written law and first identify the provisions contained in certainlaws. In this study, the data sources used are secondary data with primary,secondary and tertiary legal sources based on literature studies.From the results of research on this issue it can be concluded thatUNCLOS 1982 recognizes the right of archipelagic states (the concept of thesovereignty of archipelagic states) to draw a straight baseline of islandsconnecting the outermost points of the outer islands and this has been recognizedinternationally, which means that the exercise of sovereignty or jurisdiction ofstates bordering the strait is carried out in accordance with the provisions in thissection (part III of UNCLOS 1982) and other international legal regulations. Inaccordance with what has been proven above that the geographical position ofthe Strait of Malacca which is located in the area of Indonesia, Malaysia andSingapore where the provisions regarding the legal status for the waters that arethe straits used for international shipping we can see that as a coastal state overthe strait used for international shipping this must be in accordance with itsregulations based on the rights and jurisdiction of the coastal state and the rightsand freedoms of the country.Keywords : Strait of Malacca - International Law - UNCLOS 1982International Navigation